2006
DOI: 10.1186/1471-2121-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide attenuates nitric oxide mediated angiogenesis by blocking migration of endothelial cells

Abstract: Background Thalidomide is an immunomodulatory agent, which arrests angiogenesis. The mechanism of anti-angiogenic activity of thalidomide is not fully understood. As nitric oxide is involved in angiogenesis, we speculate a cross-talk between thalidomide and nitric oxide signaling pathway to define angiogenesis. The aim of present study is to understand the mechanistic aspects of thalidomide-mediated attenuation of angiogenesis induced by nitric oxide at the cellular level. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…In the time‐sensitive window many organs/tissues are undergoing growth and maturation and could be affected in this manner, either directly or through loss of vessels, resulting in hypoxia and cell death. This work supports that of other studies which showed disruption of actin cytoskeleton dynamics in HUVEC cells following exposure to thalidomide (Tamilarasan et al, 2006) and an antiangiogenic analog of thalidomide, CPS49 (Therapontos et al, 2009), resulting in angiogenesis failure. Thalidomide binding to tubulin could prevent cell proliferation and migration, resulting in failed tissue morphogenesis, the severity of which could be time dependent depending on vascular and tissue maturation.…”
Section: Tubulinsupporting
confidence: 91%
See 4 more Smart Citations
“…In the time‐sensitive window many organs/tissues are undergoing growth and maturation and could be affected in this manner, either directly or through loss of vessels, resulting in hypoxia and cell death. This work supports that of other studies which showed disruption of actin cytoskeleton dynamics in HUVEC cells following exposure to thalidomide (Tamilarasan et al, 2006) and an antiangiogenic analog of thalidomide, CPS49 (Therapontos et al, 2009), resulting in angiogenesis failure. Thalidomide binding to tubulin could prevent cell proliferation and migration, resulting in failed tissue morphogenesis, the severity of which could be time dependent depending on vascular and tissue maturation.…”
Section: Tubulinsupporting
confidence: 91%
“…Early exposure resulted in severely truncated limbs, even Amelia, whereas later exposure caused less severe damage, for example loss of a digit or digit tips. In fact the damage caused by CPS49 in chicken embryos was consistent with damage seen in other studies using thalidomide (Somers, 1962; Boylen et al, 1963; Merker et al, 1988; Tamilarasan et al, 2006; Therapontos et al, 2009; Vargesson, 2009, 2013; Ema et al, 2010). …”
Section: Thalidomide Is Antiangiogenicsupporting
confidence: 86%
See 3 more Smart Citations